2019
DOI: 10.1039/c8sm02450b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels composed of hyaluronic acid and dendritic ELPs: hierarchical structure and physical properties

Abstract: Hydrogels that mimic the native extracellular matrix were prepared from hyaluronic acid (HA) and amine-terminated dendritic elastin-like peptides (denELPs) of generations 1, 2, and 3 (G1, 2, and 3) as crosslinking units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…The particle size measurement analyses indicated that the coacervation of AADAAC-F4 might follow a stepwise process in which sub-micron aggregates grow into micrometer-sized coacervates. Such a stepwise process is similar to that of the dendritic thermoresponsive ELP 55 and some strong coacervatable short ELPs that we reported earlier 49 51 . In addition, DLS measurements were carried out in the presence of Cd 2+ (Fig.…”
Section: Resultssupporting
confidence: 82%
“…The particle size measurement analyses indicated that the coacervation of AADAAC-F4 might follow a stepwise process in which sub-micron aggregates grow into micrometer-sized coacervates. Such a stepwise process is similar to that of the dendritic thermoresponsive ELP 55 and some strong coacervatable short ELPs that we reported earlier 49 51 . In addition, DLS measurements were carried out in the presence of Cd 2+ (Fig.…”
Section: Resultssupporting
confidence: 82%
“…It also has a large viscosity and is viscous. When the shear rate increases, the scattered chains are rolled and contracted into a group, thereby reducing mutual hooking and the apparent viscosity, which leads to the phenomenon of shear thinning (30). There was no significant difference in the rheology of the gel at room temperature (25°C) versus normal skin surface temperature in vivo (32°C).…”
Section: Resultsmentioning
confidence: 92%
“…VEGF molecules present in the medium during gelation, may or may not be captured in the gel, depending on the interactions between the VEGF molecules and the modified alginate polymer chains. 39 In Fig. 6A it can be seen that Alg-Hep, Alg-RGD-Hep and Alg-RGD + Alg-Hep gels captured the highest amounts of VEGF.…”
Section: Kinetics Of Vascular Endothelial Growth Factor (Vegf) Releasementioning
confidence: 91%